Benthic Foraminifera in Marine Sediment Related to Environmental Changes off Bangka Island, Indonesia - K. T. Dewi; N. Nurdin; Y. A. Priohandono; A. Sinaga (Ikatan Ahli Geologi Indonesia, 2015)
Bangka Island is a famous tin island that lies offshore southeast of Sumatra. Tin mining has taken place both on land and from paleo-valleys under the sea by dredging or hydraulic method. Nearshore tin mining activities may have indirectly affected the environment, including marine organisms such as benthic foraminifera. The purpose of this study is to understand foraminifera in the sediment from offshore Sungailiat, Bangka Island as marine stress environment.A total of 25sea floor sediment samples were acquired by using a grab sampler at water depth between 6 and 26 meters.. About 300 foraminiferal shells were picked from each sample and then they were identified, calculated and documented. Some abnormal specimens were then analyzed by using EDX-SEM.The results show that there are more than 60 species which belong to 39 genera of benthic foraminifera in the study area and Rotaliida is the leading order. More than 50% of the foraminiferal shells have poor preservation or abnormal tests such as abraded, blackish, yellowish and brownish tests. Based on EDX analysis, these abnormal specimens are composed of Al2O3 (4-18%), Fe2O3 (8.87%), SiO2 (5-27%), K2O (1%), FeO (4-7%) and TiO2 (9.29%).The occurrence of abundant abnormal shells may be related to physical characteristics in the study area that are likely to affect the turbidity, nutrients and pollutants of the marine environment.